Effectiveness of Coffee Plant Extracts and Green Nanoparticles for Mosquito Control of the Dengue Vector Aedes aegypti: A Comprehensive Review (Bangladesh Journal of Infectious Diseases, 2025)
This comprehensive review examines the efficacy and environmental impact of coffee plant extracts and green nanoparticles as biocontrol agents for mosquitoes. Mosquitoes pose a significant public health threat by transmitting diseases such as malaria, dengue, Zika, and yellow fever. However, the use of insecticides for mosquito control raises concerns about the development of resistance and environmental and human health impacts. As an alternative, biocontrol strategies that utilize natural predators, parasites, and pathogens have gained attention. Coffee plant extracts have shown larvicidal, ovicidal, and repellent properties against mosquitoes, whereas green nanoparticles, particularly copper and silver nanoparticles, exhibit insecticidal activity. These alternatives offer advantages such as environmental friendliness, reduced resistance risks, and targeted mosquito species control while minimizing harm to non-target organisms. However, challenges exist in the mass production and distribution of biocontrol agents as well as their susceptibility to environmental factors. Ongoing research is aimed at developing more effective biocontrol agents for mosquito-borne disease prevention. This review provides valuable insights into the potential of coffee plant extracts and green nanoparticles for mosquito control, their efficacy, and the environmental considerations associated with their use.Bangladesh Journal of Infectious Diseases, December 2024;11(2):172-195